PENENTUAN STRATEGI PEMASARAN PRODUK 'DARMA KARYA' DENGAN MENGGUNAKAN ANALISIS GRAND MATRIX SWOT - Nur Feriyanto (Asian Journal of Innovation and Entrepreneurship, 2017)
Small Medium Entreprises (SMEs) have contributed significantly in regional and national economics. Stakeholders in the region have much expected that SMEs should play more important role as solution in decreasing unemployment and developing small scale business. Kelompok Makanan Olahan Darma Karya (Darma Karya Processing Food Business Group) in Harjobinangun Village, Pakem, Sleman, DIY is one of small medium enterprises that has been continuously received supervision from the Directorate of Research and Community Service, Universitas Islam Indonesia (DPPM UII). Over the time, the development of this business group have been much progressive. However, this group still need assistance in developing their business, viewing the fact that the business rivalry has been more competitive. In such, it is expected that the business group can further develop and contribute to the economic development in the region of  Sleman. The decision to have a proper marketing strategy is one of the efforts offered by the management and economic experts from DPPM UII in supervising Darma Karya Business Group. This marketing strategy utilizes Grand Matrix SWOT.